The Fiqh Perspective on Aurat Boundary towards Dignified Society - Pulungan, Sahmiar (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
Aurat is the minimum parts of the body that must be covered according to Allah's command. Aurat cannot be shown because it is associated with disgrace, shame and must be covered with Islamic clothing. This research discusses the perspective of fiqh regarding the boundaries of the intimate parts towards a dignified society. This research is descriptive qualitative research using a library research approach. This data is a primary data source, namely data which is the main source of library research by searching for various literature (books) and as secondary data are journals related to the research. The data collection technique uses the documentation method, namely studying and searching for data in the form of notes, documents, transcripts, books, magazines, and so on. The data analysis technique uses the Miles and Huberman model of data analysis in the data analysis technique. The results of this research are that according to the science of ushul fiqh, it can lead to obligatory 'ainy ta'abbudy, namely an obligation that must be carried out by every individual who is Muslim without asking why. Whoever carries out this obligation will receive a reward, because he has carried out the worship required by Allah SWT and whoever does not carry it out means denying one of the teachings of the religion. The daughters and wives of the Holy Prophet are model women who serve as role models for all Muslim women. Hijab is considered shari'i-qualified, when it serves to cover jewelry, clothing and the whole body.